2013
DOI: 10.1111/petr.12198
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus‐related seizure after pediatric liver transplantation – A single‐center experience

Abstract: To identify the risk factors for new-onset seizures after pediatric LT and to assess their clinical implications and long-term prognosis. The clinical and laboratory data of 27 consecutive children who underwent LT from January 2007 to December 2010 in our center were analyzed retrospectively. Patients were divided into seizures group and a non-seizures group. Pre-operative, intra-operative, and post-operative data were collected. Seizures occurred in four children, an incidence of 14.8%. All exhibited general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Although our study population was limited, our results showed that early post‐transplant hyperbilirubinemia in children who were given oral TAC is positively correlated with the development of CNI‐NCs. In support of our findings, a similar trend was seen in other studies involving both small number pediatric and large number adult populations . Hyperammonemia is also reported to alter the BBB.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although our study population was limited, our results showed that early post‐transplant hyperbilirubinemia in children who were given oral TAC is positively correlated with the development of CNI‐NCs. In support of our findings, a similar trend was seen in other studies involving both small number pediatric and large number adult populations . Hyperammonemia is also reported to alter the BBB.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, no infants under 1 year of age developed CNI‐NCs in the current study, despite comprising nearly half of the patients. Accordingly, except for NCs associated with primary disease, cerebral hemorrhage, hypoxia‐ischemic injury, or infection, CNI‐NCs in LT infants below 1 year are extremely rare in other reports as well . The reason for this result is not clear, but it is possible that the permeability of the BBB and/or brain tissue itself in infants is not amenable to the development of CNI‐NCs.…”
Section: Discussionmentioning
confidence: 97%
“…Only two of the patients showed SE or focal awareness impaired seizure, and the others were characterized as GTCSs. Xie et al [54] conducted a singlecenter retrospective study and found that of 27 pediatric recipients of liver transplantation, four patients showed seizures in the first two weeks after transplantation, and the seizures were all characterized as GTCSs. However, Kılıç et al [55] collected statistics from 28 pediatric patients and found that focal seizures were more common than generalized seizures.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…Wszolek et al [51] found that there are two peaks of seizure occurrence after transplantation, namely, the first week and the fifth to sixteenth weeks after surgery. Adult patients usually experience seizures in the early postoperative period [51,[53][54][55][56]. Xie et al [54] found that pediatric patients often show seizures within the first two weeks after liver transplantation; this idea was supported by Kılıç et al [55].…”
Section: Onset Time and Course Of Diseasementioning
confidence: 99%
See 1 more Smart Citation